PENGARUH PENGETAHUAN, KEMAMPUAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN DI BANK RAKYAT INDONESIA SYARIAH KANTOR CABANG BANDUNG SUNIARAJA - Sudirman, Miftahulhidaya; Nur'aeni, Nur'aeni (Universitas Ma'soem, 2019)
This research aims to determine the influence of knowledge, ability and experience of work to the performance of employee at BRI Syariah Bandung Suniaraja. The object of research is the performance of employees at BRI Syariah Bandung Suniaraja. This type of research is associative quantitative, the type of data is primary data, and data collection techniques in the form of observation, interviews, literature studies, and questionnaires. While the type of sample used is a saturated sample, with samples are the entire population of employees at BRI Syariah Bandung Suniaraja of 43 persons. The results showed that there was no influence between knowledge to employee performance at BRI Syariah Bandung Suniaraja, with the results of tcount <ttable (1,122 <2,023), there was no influence between ability to employee performance at BRI Syariah Bandung Suniaraja, with tcount < ttable (1,861 <2,023), there is a influence between work experience to employee performance at BRI Syariah Bandung Suniaraja, with t test results where tcount > ttable value (4,110> 2,023), and there are influence of knowledge, ability, and simultaneous work experience to employee performance at BRI Syariah Bandung Suniaraja with the results of Fcount> Ftable (5.958> 2.85).